Average Recovery Time Between Papua and Non Papuan People on Covid-19 - Edison Kabak; Isak Jurun Hans Tukayo; Guruh Suprayitno; Yoel Halitopo; Nuriati Sarlota Auparai (Sekolah Tinggi Ilmu Kesehatan Kendal, 2022)
Many research results reveal that the average recovery time of patients exposed to the Covid-19 pandemic is between 2 weeks to one month. There are many factors that affect a speedy recovery. However, there is no agreement as to whether race or ethnicity affects the accelerated healing process. To find out the comparison ofaverage recovery time between Papuans and non-Papuans exposed to Covid-19. The implications of this study may provide additional evidence of differences in recovery time between ethnicities from a nursing perspective. Used qualitative with descriptive design. The steps include identifying phenomena that exist in the community, seeking scientific references, determining respondents (14 people, 6 nurses and 8 clients each, Papuan and non-Papuan), coding, conducting semi-structured in-depth interviews, and analyzing problems comprehensively. descriptive. This research can be carried out during the Covid-19 pandemic.19in Papua Province. Description, analysis, and discussion supported by scientific journals for the last five years (2017-2022), taken from Google Scholars. Semi-structured interviews were conducted online due to restrictions during the pandemic. This study underscores four problems, namely factors that affect healing, supporting health facilities, the presence of comorbidities, and lifestyle. Our findings show that there is no difference in the length of the recovery process between Papuans and non-Papuans from Covid-19.